Abdominal wall hematoma after prone ventilation during postpartum VV-ECMO: a case report and systematic review - He, Guosen; Fan, Xuemei; Wang, Shuai; Dong, Yu (Frontiers in Medicine, 2025)
BackgroundPregnant women with ARDS are rare in themselves, and the rare complication of an abdominal wall hematoma during VV-ECMO is extremely aggressive. We report this rare case with the aim of informing clinicians to be alert to this serious complication and to share our treatment experience.Case presentationA 42-year-old Chinese woman was infected with viral pneumonia at 26 weeks of gestation, which progressed to severe ARDS. After emergency termination of pregnancy, she was placed on VV-ECMO support and ventilated in the prone position. During this period, an unexplained drop in hemoglobin occurred, so she was withdrawn from the VV-ECMO support, and was diagnosed with an abdominal wall hematoma on CT examination, which was later cured with conservative treatment.ConclusionMaternal prone abdominal wall hematoma found during VV-ECMO is rare and prone to adverse outcomes. We remind clinicians to be aware of this rare complication and prevent it.